In vitro assessment of shed sheabutter tree leaf as a potential feedstuff for goat production - Olaoye, T. S.; Yousuf, M. B.; Adeleye, O. A.; Adeyemi, K. A.; Adeyemi, A. A. (International Journal of Agricultural Technology, 2015)
The potentials of shed sheabutter tree leaf (Vitellariaparadoxa) as a feedstuff for ruminant production was evaluated using proximate chemical composition and in vitro digestibility indices. Samples of shed sheabutter leaf were analyzed for dry matter and chemical compositions to assess their feeding values for ruminant livestock production. The sheabutter leaf was further subjected to in-vitro digestion over 0, 12, 24, 36 or 48-hour period to estimate the time required for optimum degradation, using rumen fluids obtained from West African Dwarf goats. Samples were analyzed in three replicates. Results on proximate analysis indicated that shed sheabutter leaf (90.2 % dry matter) is low in crude protein (3.6 %) but high in crude fiber (27.03 %) with 56.15 % and 44.2 % Neutral Detergent Fiber, (NDF) and Acid Detergent Fiber, (ADF) levels respectively. Dry matter and organic matter losses (%) were similar (P>0.05) for the dry sheabutter leaf samples incubated at 36-hour (34.26; 35.76) or 48-hour (36.04; 37.19) period but both were higher (p<0.05) than the values obtained for samples incubated at 12-hour (15.96; 18.03) or 24-hour (23.35; 25.56) period. It was concluded that the shedshea butter leaf investigated in the present study could be fermented by the rumen microbes to serve as a source of dry matter and nutrients to ruminant livestock following appropriate supplementation. An optimum level fermentation of the dry shed butter leaf was obtained at 36-hour post-incubation period signifying that the dry leaf is to be included in ruminants’ diets at controlled levels.